EXACT SOLUTION OF THE PLANE FLOW AND SLIP FACTOR IN ARBITRARY RADIAL BLADE CHANNELS AND EXTENDED DESIGN METHOD FOR RADIAL IMPELLERS - Hetzer, Tobias; Epple, Philipp; Delgado, Antonio (2012)
Since the one dimensional mean line theory, sometimes complemented with calculations of slip factors and used for design of impellers usually leads to considerable deviations from reality the plane potential theory is used to get a better insight on the flow inside the impeller and to predict characteristic curves.Investigations presented here show that it is possible to calculate the exact solution of the plane flow and slip factor in arbitrary radial blade channels. This can be used in an extended design method for radial impellers which is suggested by the authors.